Meningkatkan Kualitas dengan Program Mencintai Buku dan Meningkatkan Minat Baca di Kalangan Anak-Anak - Hasbiyadi Hasbiyadi; Ampauleng Ampauleng; Salma Abdullah; Ansir Launtu; Syahruddin Syahruddin; Muh. Rusli Junaid; Dahniyar Dahniyar; Geraldi Geraldi; Wendy Tri Saputra (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This community service activity aims to increase interest in reading among children, especially elementary school children. This activity was carried out in Sanrobone Village, Sanrobone District, Takalar Regency, South Sulawesi and is a collaboration between STIEM Bongaya Makassar and the Sanrobone Village Government. This community service activity is packaged in the form of counseling and mentoring in an effort to increase interest in reading at an early age in one of the Elementary Schools in Sanrobone Village. There are several ways that parents must use to bring their children closer so that children are more accustomed to reading. Provide free time to read books to your children every day, Surround your children with various reading books, Make time to read with family, Make time to read with family, Provide support for their various reading activities, Get used to going to the library, Keep up with your child's reading development, Parents need to pay attention, seek help immediately if there is a problem in reading, use various methods to help your child, show your enthusiasm when your child reads his reading book. In the future, this activity is expected to continue so that interest in reading, especially among children, will increase.